Mortality from oral cancer in Aracaju/SE, Brazil: 2000-2009 - Vanessa Tavares de Gois Santos; Victor Santana Santos; Renata Alves da Silva Carvalho; Simone Alves Garcez Guedes; Cleverson Luciano Trento
INTRODUCTION: The incidence of oral cancer varies widely in the world, with two thirds of cases diagnosed in developing countries. OBJECTIVE: To investigate the epidemiology of deaths from oral cancer and the spatial distribution in the city of Aracaju in the state of Sergipe between 2000 and 2009. MATERIAL AND METHOD: Data were collected using the Mortality Information System (MIS) of Aracaju/SE at the DATASUS website and were tabulated using the software TABWIN 3.4. The geographic distribution of deaths by neighborhoods of that city was visualized. RESULT: Of the 78 deaths, 61 (78.2%) were male. The mean age was 64.23 years. Individuals of mixed ethnicity had a higher death frequency (34.6%). Regarding education, the majority of death certificates recorded the option ignored, followed by individuals with 1 to 3 years of study. The anatomical sites most affected were unspecified parts of the mouth (43.6%). The spatial distribution analysis indicated that neighborhoods such as Santos Dumont, Luzia, Atalaia, Santa Maria, Cidade Nova and Industrial had the highest death frequencies. CONCLUSION: Males between the fifth and sixth decades of life of mixed ethnicity, low education and in neighborhoods with low and very low standards of living constitute the epidemiological profile for deaths from oral cancer.